2021
DOI: 10.1007/s12144-021-02050-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender identification and attitudes toward gay people: Gender and sexuality differences and similarities

Abstract: Previous research has demonstrated the existence of gender and sexuality differences in attitudes toward gay people (which in this paper includes both lesbian women and gay men unless specified). However, these studies did not account for people with diverse genders and sexual orientations ascribing different meanings to their gender identification and its potential role in attitudes towards gay people. This study aimed to analyze the relationship between gender identification and attitudes toward gay people a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Today's Russian LGBT community faces more violence cases than ever before, including severe hate crimes (Human Rights Watch, 2014Kondakov, 2021;Russian LGBT Network, 2016). Social psychological research conducted in Russia shows that being male, living in rural areas, being religiously and politically conservative, knowing no LGBT people, and having traditional gender roles and gender attitudes are factors associated with enhanced levels of homo/ bi/transphobia (Horne et al, 2017;Gulevich et al, 2018Gulevich et al, , 2022Gulevich et al, , 2023.…”
Section: Research Activitiesmentioning
confidence: 99%
“…Today's Russian LGBT community faces more violence cases than ever before, including severe hate crimes (Human Rights Watch, 2014Kondakov, 2021;Russian LGBT Network, 2016). Social psychological research conducted in Russia shows that being male, living in rural areas, being religiously and politically conservative, knowing no LGBT people, and having traditional gender roles and gender attitudes are factors associated with enhanced levels of homo/ bi/transphobia (Horne et al, 2017;Gulevich et al, 2018Gulevich et al, , 2022Gulevich et al, , 2023.…”
Section: Research Activitiesmentioning
confidence: 99%
“…Research has revealed differences in attitudes towards sexual minorities, with heterosexual men expressing more negative attitudes than heterosexual women. In addition, other variables are also relevant, including adherence to traditional ideologies of family and gender [24,25]. Traditional gender ideologies are prevalent in societies and propose deep and persistent differences between women and men [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other variables are also relevant, including adherence to traditional ideologies of family and gender [24,25]. Traditional gender ideologies are prevalent in societies and propose deep and persistent differences between women and men [24]. Many measures of gender ideology have focused on assessing individuals' level of support for a division of family responsibilities and paid work, which is based on the belief in gendered distinct spheres [26].…”
Section: Introductionmentioning
confidence: 99%